Impact of novel systemic therapies on the first‐year costs of care for melanoma among Medicare beneficiaries. Issue 16 (27th April 2021) - Gogebakan, Kemal Caglar; Mukherjee, Kumar; Berry, Elizabeth G.; Sonmez, Kemal; Leachman, Sancy A.; Etzioni, Ruth
Abstract : BACKGROUND: Since 2011, the therapeutic landscape of melanoma has changed dramatically because of the adoption of immune checkpoint inhibitor and targeted therapies. The authors sought to quantify the effects of these changes on short‐term treatment costs by comparing the first‐year cancer‐attributable costs in novel (2011‐2015) and historical (2004‐2010) treatment eras. METHODS: The authors estimated the first‐year cancer‐attributable and out‐of‐pocket (OOP) costs by cancer stage at diagnosis by using a case‐control approach. Patients aged ≥67 years with melanoma results were used to calculate the total direct costs of treatment during the first year after the diagnosis of melanoma in the US Medicare population older than 65 years. Costs were reported in 2018 dollars. RESULTS: Costs increased with the stage at diagnosis. Average first‐year cancer‐attributable costs per patient for stage IV patients increased significantly by 61.7% from $45, 952 to $74, 297 after the adoption of novel treatments. Per‐patient OOP responsibility decreased by almost 30.8% across all stages of cancer but increased by 16.5% for stage IV patients from 2004 ($7646) to 2015 ($8911). The total direct cost of treatment for persons with melanoma older than 65 years increased by $16.03 million (4.93%) from $324.68 million in 2010 to $340.71 million in 2015. The largest increase in yearly total cost, $23.64 million (56.53%), was observed among stage IV patients. CONCLUSIONS: The direct cost of melanoma increased significantly in the Medicare population, particularly for advanced‐stage disease. Prevention and early detection initiatives may reduce the economic burden of melanoma. Abstract : This study quantifies the effects of the adoption of novel immune checkpoint inhibitor and targeted therapies on short‐term treatment costs of melanoma in the Medicare population. The results reveal that the direct cost of melanoma increases significantly, particularly in advanced‐stage disease.